Integrating New Approach Methodologies to Address Environmental Pancreatic Toxicity and Metabolic Disorders - Yue Ge (Biology)
Advancing our understanding of pancreatic toxicity and metabolic disorders caused by environmental exposures requires innovative approaches. The pancreas, a vital organ for glucose regulation, is increasingly recognized as a target of harm from environmental chemicals and dietary factors. Traditional toxicological methods, while foundational, often fail to address the mechanistic complexities of pancreatic dysfunction, particularly under real-world conditions involving multiple exposures. New Approach Methodologies (NAMs)—including high-throughput screening (HTS), OMICS technologies, computational modeling, and advanced in vitro systems—offer transformative tools to tackle these challenges. NAMs enable the identification of mechanistic pathways, improve testing efficiency, and reduce reliance on animal testing. This commentary explores the integration of NAMs into pancreatic toxicity screening, addresses critical gaps in evaluating the cumulative risks of chemical and dietary exposures, and proposes solutions for integrating the pancreas into toxicity screening through NAMs. By highlighting recent advancements and emphasizing their adoption in environmental toxicity assessment frameworks, this work demonstrates the potential of NAMs to revolutionize environmental health research, inspire interdisciplinary collaboration, and protect public health.